OBSERVATIONAL STUDY OF POST-COVID-19 SYNDROME IN HEALTH CARE WORKERS INFECTED WITH SARS-COV-2 VIRUS: GENERAL AND ORAL CAVITY COMPLICATIONS - Maria Valentina Popa; Elena Roxana Bogdan Goroftei; Cristian Guțu; Mădălina Duceac; Constantin Marcu; Mihaela Roxana Popescu; Daniela Druguș; Letiția-Doina Duceac (Romanian Society of Oral Rehabilitation, 2023)
Post-COVID-19 syndrome encompasses a variety of conditions that can affect people with a history of probable or confirmed SARS-CoV-2 infection, usually within 3 months of the onset of COVID-19, with symptoms that last at least 2 months and cannot be explained by an alternative diagnosis, with a major impact on daily and occupational activities. Material and methods: long-COVID symptoms among healthcare professionals in an emergency clinical hospital and the influence on work activities were assessed. Results: 42% had more than 2 long-standing symptoms. In the majority of cases the symptoms disappeared after 2-3 months, with 10% experiencing persistence of symptoms at 6 months, 5% even at 12 months. The most common symptom reported was fatigue, followed by sensory disorders (parosmia and dysgeusia), arthralgia, sleep disturbances, stress, headache, dizziness. Discussions: The work capacity of employees who experienced long-term symptoms were influenced. Difficulties in performing tasks, maintaining work rhythm and working night shifts led in some cases to temporary work/workplace adaptation measures to allow affected employees to recover. As for post-COVID-19 oral complications, they can affect not only comfort but also general health through their impact on nutrition, oral hygiene and psychological state. Conclusions: In the long term, post-COVID syndrome represents a significant challenge for the whole health system and society, where their health and well-being are essential to ensure the continued availability of quality health care.